Environmental education in plastic elementary education cuban. Positive and good practice experiences - Torres Gutiérrez, Alberto; Moré Estupiñán, Mavel; Torres Díaz, Noevia (Avances en Supervisión Educativa, 2014)
Current environmental issues require strengthening the work of environmental education at different educational systems of the XXI century. To this end , it is crucial the work to be performed , from the earliest ages and considering the relationship between the different subjects of the school curriculum . Therefore, the Environmental Education stated general objective in the Cuban Model Elementary School, that is treated with an interdisciplinary character. Based on existing even in achieving these purpose limitations, a study / research leading to the development of scientific result presented is performed. The criteria of experts and the results of the application in practice, confirmed the relevance, importance and effectiveness of the system of activities that promotes Plastic Education Environmental Education school 4. Grade ENU " Hurtado de Mendoza" Township santa Clara, Villa Clara province, Cuba.